PEMBUATAN MEDIA VIDEO TUTORIAL UNTUK PERHITUNGAN PERENCANAAN JALAN BARU PADA MATA KULIAH KPJR DI JURUSAN TEKNIK SIPIL FT-UNP - Mochamad Hermansyah; Oktaviani .; Totoh Andayono (Universitas Negeri Padang, 2018)
Abstract—This reseach aims to produce a valid video tutorial-based learning media on the subject of KPJR with material of new road planning at FT-UNP Civil Engineering department. The research employs descriptive method. The data analysis is aimed to 34 samples of the building (D3) study program who are taking KPJR subject by giving media in the form of video tutorial and learning evaluation question (10 items of objective and 1 essay question) related to the material. Before the media was distributed, the first thing to do was validationof content by 2 validator that was a KPJR lecturees and afterthat validation of media by a lecturer . The result are 0,933 in terms of media and 0,844 in terms of material. The result of the evaluation obtained with the average value of 71,82 (categorized well)that means the video can already be used and published as one of the media that can help students to understand the material. Keywords:Video Tutorial, Flexible Pavement